Saling Menghormati di dalam Kasih Kristus: Tafsiran Feminis atas teks Efesus 5: 22-33 - Yosa Marianta Hetharie (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
This paper offers a reinterpretation of the text of Ephesians 5: 22-33 in a feminist frame, especially in the phrases “submit” and “head”. These two words are often used as an excuse to justify acts of subordination and even violence against women. The method used is Elisabeth Schüssler Fiorenza's Fiorenza's feminist hermeneutics, especially the hermeneutic model of suspicion. Reinterpretation efforts using the hermeneutic model aim to investigate more deeply the use of these words in the text and context in which they are written. The result is to offer an understanding that no longer puts women in a corner, and even perpetuates various forms of violence against women. The conclusion from this reinterpretation effort is that the text of Ephesians 5: 22-33 emphasizes mutual-submission to one another to the love of Christ.